Examining the impact of using social networks on political knowledge and political attitude by Iranian university students - Alami, Abdolreza; Hamedi Mohd Adnan,; Kotamjani, Sedigheh Shakib (Penerbit Universiti Kebangsaan Malaysia, 2019)
Social Network Sites (SNSs) play key role to raise individuals’ awareness in terms of political issues around the world. Young generation particularly university students utilize social networks for political activism and discussion. The present study investigates the effect of social network on political knowledge and attitude of Iranian university students. Mixed- method design was employed to collect quantitative data through a questionnaire followed by an emailed interview with Iranian media experts. The sample size in the study consisted of 382 Iranian students and 12 media experts. The findings of the current study showed that there is generally a direct and positive relation between the level of use of social networks and political knowledge, and attitude. Moreover, the results revealed that using social network sites have a significant positive effect on student’s level of political knowledge and political knowledge mediates the positive effect of social network use by Iranian university students on their political behavior. The results of interview corroborate that easy access to modern information sources has increased political knowledge of the students. The results also implied the necessity of deploying an intelligent filtering rather than indiscriminate blocking of the social network websites.